Mengembangkan Ayam Buras Dan Sapi Potong Untuk Meningkatkan Pendapatan Petani Kabupaten Maros - Purwanti, Sri -; Nompo, Syamsuddin; Agustina, Laily; Hidayat, Muh. Nur (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
The activities conducted in Maros regency Tanralili district Purnakarya village in chickens and beef cattle groups Cedde Jaya. The main source of livestock feed cows during the dry season are dry forage, rice straw, corn straw and hay crops of nuts which happened to be planted at the time of drought. Besides, leaf  Gamal is also a main feed in dry  season. Number of cattle per family ownership only 2-3  head extensively maintained. Range chicken as well as extensive maintenance, ownership on average 2-5 chicken each household group.  To increase the productivity of cattle, the team provides counseling, coaching, training and mentoring as well as providing some main of facilities such as cattle shed, biogas digester, planting banana. Results are expected in the presence of  activities is the avaibility of green forage mainly during the dry season, so that the cattle population will increase, the biogas as a fuel  alternative to kerosin and LPG gas, liquid and solid fertilizer from biogas by-product process, the increasing population of chicken qualified (meat and eggs as well as the day old chick).  Besides the problem of production is also done on the farm management. The activities is expected that will increase the incomes of farmers further improve the welfare of Maros regency. For the sustainability of the program it is necessary supervision and guidance are routinely performed by the related department along with the college.